Joint Range of Motion and Patellofemoral Pain in Dancers - Steinberg, N.; Siev-Ner, I.; Peleg, S.; Dar, G.; Masharawi, Y.; Zeev, A.; Hershkovitz, I. (International Journal of Sports Medicine, 2012)
The aim of the present study was to determine the association between joint range of motion (ROM) and patellofemoral pain syndrome (PFPS) in young female dancers. The study population included 1 359 female dancers, aged 8–20 years. All dancers were clinically examined for current PFPS, and their joint ROM was measured at the lumbar spine and the lower extremities. 321 of the 1 359 dancers (23.6%) experienced PFPS. Prevalence of the syndrome increased with the dancer’s age (p<0.001). Dancers with hypo ROM in hip external rotation, ankle plantar-flexion, ankle/foot pointe, hip abduction, hip extension, and limited hamstrings and lumbar spine were significantly less prone to developing PFPS compared to dancers with average ROM: 19.2% vs. 26.2% (p=0.014); 13.7% vs. 26.1% (p<0.001); 12.2% vs. 26.2% (p<0.001); 10.0% vs. 25.3% (p<0.001); 12.6% vs. 24.2% (p<0.001); and 9.3% vs. 28.2% (p<0.001), respectively. The group with the smallest prevalence of PFPS (10.2%) manifested restricted ROM at both the hip and ankle/foot joints. Dancers with decreased hip and ankle/foot joints ROM are less prone to develop PFPS. When making an association between joint ROM and injuries, not only the ROM at the targeted joint should be considered, but also the ROM at neighboring joints.
Keywords: injuries; dance; knee joint; joint range of motion; patellofemoral pain syndrome